2017
DOI: 10.1038/srep44535
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the abundance of airborne pollen and fungal spores at variable elevations using an aircraft: how high can they fly?

Abstract: Airborne pollen and fungal spores are monitored mainly in highly populated, urban environments, for allergy prevention purposes. However, their sources can frequently be located outside cities’ fringes with more vegetation. So as to shed light to this paradox, we investigated the diversity and abundance of airborne pollen and fungal spores at various environmental regimes. We monitored pollen and spores using an aircraft and a car, at elevations from sea level to 2,000 m above ground, in the region of Thesssal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 47 publications
1
61
1
1
Order By: Relevance
“…The height declines during the afternoon coincident with a southerly sea breeze, but is still above 1200 m at 17:00 AEDT. The nocturnal boundary layer is around 200 m. Over 77 % of grass pollen is found at ground level (Damialis et al, 2017) due to its size and density. The lifetime of our model pollen over 1 km is 6 h. The model RH is more negatively correlated with grass pollen levels (average r = −0.52) than is observed.…”
Section: Observed and Modelled Pollen Correlations With Meteorologymentioning
confidence: 99%
See 1 more Smart Citation
“…The height declines during the afternoon coincident with a southerly sea breeze, but is still above 1200 m at 17:00 AEDT. The nocturnal boundary layer is around 200 m. Over 77 % of grass pollen is found at ground level (Damialis et al, 2017) due to its size and density. The lifetime of our model pollen over 1 km is 6 h. The model RH is more negatively correlated with grass pollen levels (average r = −0.52) than is observed.…”
Section: Observed and Modelled Pollen Correlations With Meteorologymentioning
confidence: 99%
“…Victoria had ex-perienced the world's largest epidemic thunderstorm asthma event. In the aftermath, the state government funded better planning of healthcare resources to improve preparedness and response arrangements for similar events in the future (Davies et al, 2017;Lindstrom et al, 2017). This plan included the development of a pilot thunderstorm asthma early-warning service using statistical pollen forecasts , operated by the Bureau of Meteorology (BOM), and the concurrent development of a pollen forecasting system, built around pollen emission and transport modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Die Strategie der Allergenvermeidung ist bei Nahrungsmitteln, Tierhaaren oder Duftstoffen besonders effektiv, jedoch wenig wirksam bei luftgetragenen Pollen [4]. Die geringe Pollenkorngröße (Abb.…”
Section: Transfer In Die Praxis Von Prof Dr Claudia Traidl-hoffmannunclassified
“…Inadequate forecasts concerning the expected pollen concentration are regarded as a considerable health risk for pollen allergy sufferers (Bastl et al, 2017). Damialis et al (2017) just recently reported the first basic experiments measuring pollen concentrations at considerable altitudes above ground level by using a manned aircraft. However, this research has shown that the use of a manned aircraft in densely populated areas is limited and further requires considerable organizational and financial effort.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, particle collection with subsequent particle-type identification and quantification has an advantage over particle counting, at least as long as reliable in situ particle identification is not available. First attempts to collect bioaerosol particles using a pollen trap mounted on a fixed-wing UAV are described in Gottwald and Tedders (1985). Another way to realize the collection of airborne particles is to use a tethered balloon with rotating rods for capturing airborne pollen grains (Comtois et al, 2000).…”
Section: Introductionmentioning
confidence: 99%